Effect of Compression Ratio on the Performance and Emission Characteristics, and Cycle-to-Cycle Combustion variations of a Spark-Ignition Engine Fueled with Bio-methane Surrogate. (5th February 2019) - Gupta, Sachin Kumar; Mittal, Mayank
Highlights: A comparative study of SI engine characteristics fueled with gasoline and bio-methane surrogate. Effect of compression ratio (CR) on engine characteristics under bio-methane surrogate. Statistical analysis of cycle-to-cycle combustion variations at low load. A higher CR is found to be effective for reducing cycle-to-cycle variations at low operating loads. Abstract: Low-carbon fuels such as bio-methane, obtained from biomass gasification consisting 96–98% of methane by volume, is a promising alternative fuel for internal-combustion engines. In the present work, methane is used as a surrogate of bio-methane for studying the engine characteristics. First, a comparative study was performed on a single-cylinder, water-cooled, variable compression ratio, spark-ignition engine operating under methane and gasoline fuels with compression ratio (CR) of 8.5:1. Subsequently, the effect of compression ratio was investigated on the performance, combustion including cycle-to-cycle combustion variations through statistical analysis, and emissions, when engine was operated over a wide load range at 8.5:1, 10:1 and 12:1 CRs under methane. It was found that the brake specific energy consumption and emissions were reduced for methane compared to gasoline at all operating loads. Results showed that when the CR was increased from 8.5:1 to 12:1 at low operating load of 5 N-m, brake specific fuel consumption was reduced by 7.2% and the average location of peak in-cylinder pressure ( θ p max ) was shifted towards the TDC, i.e. 17.4 to 13.5 CAD ATDC, with a decrease in cycle-to-cycle combustion variations. In addition, θ p max showed linear and quadratic relationships with peak in-cylinder pressure and IMEP, respectively.